Evaluation of Commercial Disinfectants Against Fungal Pathogens Isolated from Broiler Farms - Soliman, Essam S.; Sobeih, Mohamed A.A.; Ahmad, Z.H.; Hussein, M.M.; Abdel-Latiff, H. (International Journal of Poultry Science, 2009)
Three different concentrations of five commercial disinfectants [TH4® 2, 1 and 0.5% (combination of quaternary ammonium compounds and gluteraldhyde), Microzal® 2, 1 and 0.5% (combination of quaternary ammonium compounds and gluteraldhyde), Incospect IC 22XA 2, 0.5 and 0.25% (combination of quaternary ammonium compounds, gluteraldhyde and formalin), Povidone Iodine® 5, 7.5 and 10% (iodophore) and Formalin® 3.7, 2.5 and 1.8% (commercial formaldehyde 37%)] were tested in a laboratory trials against two fungal isolates (Aspergillus niger and Candida albicans) at concentration of ( 105) isolated during epidemiological surveillance in broilers farms. The trials were carried in the presence and absence of organic matter (dried yeast 5%) using MIC use-dilution test. Minutely samples were collected for the fungal counts. In the absence of organic matter, TH4® 2, 1 and 0.5% achieved 100% efficacy after 5, 5 and 10 min (p<0.001) respectively against Aspergillus niger and Candida albicans. Microzal® 2, 1 and 0.5% achieved 100% efficacy after 5, 10 and 20 min (p<0.001) respectively against Aspergillus niger and after 5 min (p<0.001) against Candida albicans. Incospect IC 22XA 2%, 0.5% and 0.25% achieved 100% efficacy after 5 min (p<0.001) against Aspergillus niger and after 5, 5 and 10 min (p<0.001) respectively against Candida albicans. Povidone Iodine® 10, 7.5 and 5% achieved 100% efficacy after 5, 5 and 20 min (p<0.001) respectively against Aspergillus niger and after 5, 5 and 20 min (p<0.001) respectively against Candida albicans. Formalin® 3.7, 2.5 and 1.8% achieved 100% efficacy after 5, 10 and 10 min (p<0.001) respectively against Aspergillus niger and after 5, 5 and 10 min (p<0.001) respectively against Candida albicans. In the presence of organic matter, TH4® 2, 1 and 0.5% achieved 100% efficacy after 5, 10 and 20 min (p<0.001) respectively against Aspergillus niger and after 5, 5 and 20 min (p<0.001) respectively against Candida albicans. Microzal® 2, 1 and 0.5% achieved 100% efficacy after 5, 20 and 20 min (p<0.001) respectively against Aspergillus niger and after 5, 10 and 10 min (p<0.001) respectively against Candida albicans. Incospect IC 22XA 2, 0.5 and 0.25% achieved 100% efficacy after 5 min (p<0.001) against Aspergillus niger and after 5, 5 and 10 min (p<0.001) respectively against Candida albicans. Povidone Iodine® 10, 7.5 and 5% achieved 100% efficacy after 30 min (p<0.001) against Aspergillus niger and Candida albicans. Formalin® 3.7, 2.5 and 1.8% achieved 100% efficacy after 5, 10 and 20 min (p<0.001) respectively against Aspergillus niger and after 5, 5 and 20 min (p<0.001) respectively against Candida albicans. The results revealed that Incospect IC 22XA was the superior in the efficacy and the fastest disinfectant to achieve the 100% killing against the two organisms.